Je suis president an analysis of the editorial cartoons on Noynoy Aquino and Duterte in the Philippine broadsheets Luigi Renzo Naval ; Rachel E. Khan, adviser. - Naval, Luigi Renzo 1996-; Khan, Rachel E. (2018)
"Editorial cartoons serve as platforms for cartoonists and newspapers to discuss current political and social issues or to call for societal reforms. This way, history is then recorded in an artistic form. With the scarcity of analysis of cartoons in the country, it is necessary to conduct one using editorial cartoons during the last decade. This study analyzed the portrayals of the editorial cartoons of Philippine Daily Inquirer, The Philippine Star and Manila Times on presidents Benigno Simeon Aquino and Rodrigo Duterte during their first years in power. The cartoons that were examined are dated from July 1, 2010 until June 30, 2011 for Aquino and July 1, 2016 until June 30, 2017 for Duterte. These times frames could show any changes in the cartoons' portrayals in terms of tone, theme, and criticism, and political beliefs of the publications and the cartoonists. To examine the editorial cartoons of the three newspapers, the study was guided by Ferdinand de Saussure's theory of Significtion (as developed by Roland Barthes), which looked at the denotation, connotation and myth of the cartoons. Denotation explains the literal and obvious meaning of the cartoons while connotation is about the emotions attached to the cartoons and how they were drawn, and the myth explains the culture and personal beliefs used to be the basis in order to conceptualize the cartoons. In gathering the data needed for this study, the researcher used two methods: content analysis and interview with the cartoonists. The content of the editorial cartoons thaw were collected were be analyzed through the Signification theory, and afterwards the cartoonists interviewed to gather information that the content analysis may have missed out."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Editorial cartoons